2004
DOI: 10.4269/ajtmh.2004.71.558
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Cutaneous Leishmaniasis Due to Leishmania Guyanensis: Case of a Patient With 425 Lesions

Abstract: Disseminated cutaneous leishmaniasis is characterized by the presence of a large (> or =10) number of lesions at several anatomic sites (head, limbs, and trunk). Most of the lesions are small, papular, and appear simultaneously with or secondarily to one or several ulcerated lesions of localized cutaneous leishmaniasis. We report the first case of disseminated cutaneous leishmaniasis in French Guiana. It concerns a 24-year-old woman who tested negative for human immunodeficiency virus (HIV). The disease began … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 10 publications
1
41
0
5
Order By: Relevance
“…The lesions described so far range from isolated papules, plaques or ulcers on exposed areas similar to those found in nonimmunosuppressed patients or in nonHIVinfected patients 7,14,15 to disseminated ulcers or plaques. 16,17 Frequently, cutaneous lesions in HIV-infected patients are associated with visceral leishmaniasis resembling postkala-azar dermal leishmaniasis. 18,19 As the clinical manifestations of tegumentary leishmaniasis in HIV-infected patients are likely to be dependent on immunological status, and as the presence of severe immunosuppression may modify the clinical characteristics of the disease, hindering the diagnosis of tegumentary leishmaniasis by physicians, we investigated tegumentary leishmaniasis in HIV-infected patients, focusing on clinical manifestations, diagnosis, immunological status and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions described so far range from isolated papules, plaques or ulcers on exposed areas similar to those found in nonimmunosuppressed patients or in nonHIVinfected patients 7,14,15 to disseminated ulcers or plaques. 16,17 Frequently, cutaneous lesions in HIV-infected patients are associated with visceral leishmaniasis resembling postkala-azar dermal leishmaniasis. 18,19 As the clinical manifestations of tegumentary leishmaniasis in HIV-infected patients are likely to be dependent on immunological status, and as the presence of severe immunosuppression may modify the clinical characteristics of the disease, hindering the diagnosis of tegumentary leishmaniasis by physicians, we investigated tegumentary leishmaniasis in HIV-infected patients, focusing on clinical manifestations, diagnosis, immunological status and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, some Leishmania species mainly in the New World can cause a more disseminated disease in the host producing very large numbers of lesions, i.e. up to 425 in a single individual [6]. In general, the pathological changes characterizing the various clinical forms of leishmaniasis reXect the balance between parasite multiplication, the immune response of the patient and the resulting degenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…With about 300 cases of human cutaneous leishmaniasis (HCL) reported annually (Carme 2001, Lightburn et al 2001) and some extreme situations (Couppié et al 2004), this disease still represents a major public health problem in French Guiana. The first HCL cases were confirmed in French Guiana in 1943 (Floch 1943) and past studies showed that Leishmania (Viannia) guyanensis is the predominant species of Leishmania (Floch 1957, Dedet et al 1989, Raccurt 1996 and L. (V.) naiffi have also been diagnosed (Dedet et al 1985, Raccurt et al 1995, Basset et al 2001, Pratlong et al 2002.…”
mentioning
confidence: 99%